Analisis SWOT terhadap Implementasi Teknologi Blockchain sebagai Alat Pencegahan Fraud pada Sistem Akuntansi - Suginam Suginam; Rosasmanizan binti Ahmad; Rizky Indra Saputra (Journal of Management and Economics Research, 2025)
This study aims to analyze the implementation of blockchain technology as a tool for fraud prevention in accounting systems by employing a SWOT analysis framework to evaluate its strengths, weaknesses, opportunities, and threats. The main research problem arises from the growing complexity of accounting fraud in the digital era and the limitations of traditional accounting systems in providing transparency and data security. The findings indicate that blockchain offers strengths in enhancing transparency, accountability, and real-time auditing, but faces weaknesses such as high implementation costs and low digital literacy. On the other hand, new regulatory frameworks and global digital transformation present significant opportunities, while regulatory uncertainty and cybersecurity risks remain critical threats. The SWOT analysis was further developed into actionable strategies, including the adoption of triple-entry bookkeeping, real-time digital audits, hybrid blockchain, and blockchain-based forensic accounting. The novelty of this study lies in the integration of SWOT analysis with measurable operational indicators, enabling future empirical testing, as well as the development of a conceptual model that maps derivative strategies for blockchain-based fraud prevention in accounting.